An Analysis of the Impact of Legal Reforms on Corporate Governance in Indonesia - Silitonga, Saritua (LPPM Universitas Ekasakti Padang, 2024)
This study aims to determine the relationship between the implementation of good governance based on employment contracts, bureaucratic reform and e-government to improve the efficiency of government administration in Indonesia. This research also uses qualitative research methods with data collection methods in the form of describing analysis methods, describing and discussing, and on the basis of relevant literature review, studying and collecting data taken from articles published in various scientific journals and book compilations. Secondary data referenced from the relevant literature review is used as a tool. Indonesia has implemented work contract-based bureaucratic reform in an effort to improve government administration. Bureaucratic reform based on work contracts, where the government organizers, such as regional heads, are always required to achieve the pre-determined work goals. The results of this study show that in implementing bureaucratic reform to achieve good governance, the Government uses the concept of working contract. By using the concept of employment contract that uses technology (e-government), the employment contract can be more transparent with the output in the form of work evaluation. This is shown from several points of view, as use of electronic government related to establishment of good governance practices, implementation of good governance related to bureaucracy institutional transformation, there is a relationship between performance and electronic government, performance with bureaucracy transformation, and implementation of good governance with performance.